Penerapan Model Pembelajaran Student Team Achiement Division (STAD) untuk Meningkatkan Hasil Belajar Siswa Materi Puasa pada Siswa Kelas VIII-B MTs Negeri Sinabang - Bahat (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2021)
The Student Teams Achievement Divisions (STAD) Cooperative Learning Model is one of the types of cooperative learning that shares students in several small groups heterogeneous consisting of 4-5 group members. The purpose of this research is to improve student learning outcomes by applying STAD's learning model, fasting material in grade VIII-B students MTsN Sinabang. This research is a class action study conducted in two cycles and each cycle consists of four phases, namely the planning stage, the implementation of action, observation and reflection. The number of study subjects was 23 people consisting of 12 students and 11 schoolgirls. The data collection techniques used are tests and observations. The results showed that students ' learning results at an initial condition of 47.8%, Cycle I reached 73.9%. In the second cycle, there is an increase in the better direction of reaching 91.3%. It can be concluded that the application of the learning model STAD can improve student learning outcomes in the fasting material in students of class VIII-B MTsN Sinabang.